Data set from a bedload tracer field study in an alpine section of the Drava River in 2017 and 2018 - Mario Klösch; Sebastian Pessenlehner; Philipp Gmeiner; Helmut Habersack (PANGAEA, 2024)
This is a data set from a bedload tracer field study in an alpine section of the Drava River. It contains the characteristics and changing positions of transported bedload tracers, the grain sizes of the river bed surface and a time series of the bed shear stress. A number of 65 artificial bedload tracers were equipped with active very high frequency radio transmitters imitating 5 natural grains representative of five grain size classes. The tracers were all seeded on 11 May 2017 in a cross-section across five points in the middle of the river, 2.5 m apart laterally. Seeding was done from a boat in bags that contained the tracers and could be opened after they were lowered onto the riverbed. After seeding, 10 searches by boat up to 11 June 2018 resulted in total distances of up to more than 30 km. Grain size distributions of the riverbed surface were determined by Wolman Pebble Counts at 9 different locations in wadeable waters at low flow. The time series of bed shear stress was calculated for the seeding site and obtained from water depths modelled with a one-dimensional hydrodynamic-numerical model and a channel slope obtained from the analysis of cross-sections. The shear stress can also be calculated for cross-sections downstream of the seeding location by using the functions available in the corresponding publication. In the publication, this data set was used to derive a formula for the unsteady virtual velocity of the tracers, taking into account the deceleration due to mixing and advection. The description of bedload transport as a relay run in contrast to the individual runs of the decelerating tracers also made it possible to distinguish between the unsteady virtual velocity of bedload and the unsteady virtual velocity of decelerating bedload tracers.